Ketangguhan Mental Siswa Pencak Silat IKSPI Kera Sakti Kategori Tanding Ditinjau dari Tingkatan Sabuk - Fitria Nur Arimbi; Anna Noordia; Yetty Septiani Mustar; Awang Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Pencak silat is a martial art that involves physical and emotional combat. This study aims to explore the mental toughness of pencak silat students in the category of matches based on the belt level they have. The main focus of the study is the relationship between emotional intelligence, concentration, and mental toughness among students with black and yellow belts. The method used was a questionnaire targeting 140 male students from the IKSPI Kera Sakti school in Taman District, Sidoarjo. The results showed that black belt students had better mental toughness than yellow belt students, especially in facing challenges. These findings are expected to help coaches design more effective training programs, as well as increase awareness of the importance of psychological support in achieving achievement. This study provides important insights into the psychological factors that play a role in the performance of pencak silat athletes and opens up opportunities for further research in the field of sports psychology.